2019
DOI: 10.1037/xhp0000607
|View full text |Cite
|
Sign up to set email alerts
|

The limits of super recognition: An other-ethnicity effect in individuals with extraordinary face recognition skills.

Abstract: The University of Gloucestershire accepts no liability for any infringement of intellectual property rights in any material deposited but will remove such material from public view pending investigation in the event of an allegation of any such infringement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
35
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 62 publications
11
35
1
Order By: Relevance
“…The findings are also important from a theoretical point of view, contributing to the debate about possible differences in the way typical and super-recognisers process faces (e.g., Bate et al, 2019;Bobak, Bennetts et al, 2016;Bobak, Hancock et al, 2016;Bobak, Parris, Gregory, Bennetts, & Bate, 2017;Robertson et al, 2019;Russell et al, 2009). Our data does not fully support the hypothesis put forward by Bobak, Hancock et al (2016) that superrecognisers are better than typical recognisers at structural encoding and can construct viewindependent representations from static images.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The findings are also important from a theoretical point of view, contributing to the debate about possible differences in the way typical and super-recognisers process faces (e.g., Bate et al, 2019;Bobak, Bennetts et al, 2016;Bobak, Hancock et al, 2016;Bobak, Parris, Gregory, Bennetts, & Bate, 2017;Robertson et al, 2019;Russell et al, 2009). Our data does not fully support the hypothesis put forward by Bobak, Hancock et al (2016) that superrecognisers are better than typical recognisers at structural encoding and can construct viewindependent representations from static images.…”
Section: Discussioncontrasting
confidence: 79%
“…There are also theoretically important reasons to establish whether there are qualitative differences in face processing between typical and super-recognisers. Research focusing on the other-ethnicity bias provides evidence that typical and super-recogniser performance does not differ in a qualitative way, and both groups are subject to the same influences; recognition memory in both groups was better for own-than other-ethnicity faces (Bate et al, 2019;Robertson, Black, Chamberlain, Megreya, & Davis, 2019). Other studies have observed a heightened inversion effect in super-recognisers (Russell, Duchaine, & Nakayama, 2009), and it has been suggested that they rely more on holistic processing (Bobak, Bennetts, Parris, Jansari, & Bate, 2016).…”
Section: A Novel Interactive Face Matching Proceduresmentioning
confidence: 93%
“…Ramon, Bobak, and White () offer a timely review of superior face recognition, concluding that current interest in real‐world deployment of ‘super‐recognizers’ (SRs) is not supported by the current academic literature. Here, we agree with the authors’ caution, not only because of the sparsity of SR investigations, but also in the light of recent empirical work from our group that questions the consistency (Bate & Dudfield, ; Bate, et al ., ), homogeneity (Bate et al ., ), and limitations (Bate, et al ., ) of superior face recognition performance. Ramon et al .…”
mentioning
confidence: 99%
“…This pattern challenges current notions of the development of perceptual expertise and suggests that the improvements for native stimuli may occur independently of the decrements for nonnative stimuli. Such independence has been shown for superrecognizers, whose superiority for the native category (adult own race upright faces) co-occurs with superior processing of infants' faces (45) and other races' faces (46). In adults with synesthesia, connections underlying the discrimination of items from native categories might have been strengthened by the normal consolidation of experienced categories without the full complementary pruning of inexperienced ones.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, the independence of tuning in to native categories and of tuning out of nonnative categories is evident in human adults labeled superrecognizers because of their extraordinary ability to recognize facial identity for native categories (e.g., adults, same race, upright). They are also superior at recognizing faces from rarely experienced categories, namely infants' faces (45) and other races' faces (46), with no correlation among these abilities.…”
Section: Significancementioning
confidence: 98%